Uprooting Without Proletarianization in the Paraguayan Agricultural Sector - Ramón Bruno Fogel Pedroso (Íconos)
This article analyzes the peculiarities of neo-extractivism in Paraguay and its effects on the reconfiguration of class structure, specifically the uprooting of peasants without proletarianization, which can lead to scenarios of conflict. This project is based on secondary data from the last years (2001-2016) when the departure of over-accumulation required there to be a movement of capital in order to search for new spaces to exploit natural resources. Since then, transgenic soy in Paraguay has continued to expand, making Paraguay the country with the most transgenics in the world in terms of the proportion of surface area that is used for these types of crops.